Proposal for Urban Subcenters identification based on the Spatial Distribution Of Functions: Case of Maputo City - Mozambique - Chicombo, Tomé Francisco (Sociedade & Natureza, 2021)
This study presents a methodological proposal for identification of new urbanfunctional centralities based on data from the points of interest of Open Street Map platform.On the other hand, data collected through fieldwork interviews were also used for the studyand complemented with Google Earth imagery. Points of interest data were classifiedaccording to pre-defined criteria representing urban features. Each criterion was assigned aweight. The criteria weights were calculated based on the Analytical Hierarchical Process(AHP) method. For this purpose, interviews were carried out with specialists and individualswith greater experience of living in the study area, based on their perception regarding tothe distribution of urban functionalities. The results of interviews were introduced inmatrices that allowed the calculation of weights for each criterion. In addition, points ofinterest data were edited and processed through ArcGis application, in which a map wasproduced showing the spatial distribution of the points of interest and the respective levelsof centrality. Therefore, it was possible to identify from this study some points ofconcentration outside the historic center of the Maputo city, which show evidence ofemergence of new functional centralities as a result of implementation of new urbaninfrastructure in the non-central area, mainly related to commerce and services provision.